A techno-economic study of the strategy for hydrogen transport by pipelines in Canada - Cheng, Winston; Cheng, Y. Frank (Journal of Pipeline Science and Engineering, 2023)
•Analyzed the various hydrogen transportation methods.•Suggested the optimal option for hydrogen transport in Canada.•Discussed the technical challenges when repurposing existing pipeline for hydrogen transport. Hydrogen, as a clean, zero-emission energy fuel, will play a critical role in energy transition and achievement of the net-zero target in 2050. Hydrogen delivery is integral to the entire value chain of a full-scale hydrogen economy. This work conducted a systematic review and analysis of various hydrogen transportation methods, including truck tankers for liquid hydrogen, tube trailers for gaseous hydrogen, and pipelines, by identifying and ranking the main properties and affecting factors associated with each method. It is found that pipelines, especially the existing natural gas pipelines, provide a more efficient and cheaper means to transport hydrogen over long distances. Analysis was further conducted on Canadian natural gas pipeline network, which has been operating for safe, effective, and efficient energy transport over six decades. The established infrastructure, along with the developed operating and management experiences and skillful manpower, makes the existing pipelines the best option for transport of hydrogen in either blended or pure form in the country. The technical challenges in repurposing the existing natural gas pipelines for hydrogen service were discussed, and further work was analyzed.